Onosma L.: A review of phytochemistry and ethnopharmacology - Kumar, Neeraj; Kumar, Rajnish; Kishore, Kamal (Pharmacognosy Reviews)
The genus Onosma L. (Boraginaceae) includes about 150 species distributed world‑wide in which only about 75 plants has been described for its morphology and less than 10 plants for their chemical constituents and clinical potential. The phytochemical reports of this genus revels that it comprise mainly aliphatic ketones, lipids, naphthazarins, alkaloids, phenolic compounds, naphthoquinones, flavones while most important are shikonins and onosmins. The plants are traditionally used as laxative, anthelmintic and for alexipharmic effects. The plants are also equally use in eye, blood diseases, bronchitis, abdominal pain, stangury, thirst, itch, lecoderma, fever, wounds, burns, piles and urinary calculi. The flowers of various plants are prescribed as stimulants, cardiotonic, in body swelling while leaves are used as purgative and in cutaneous eruptions. The roots are used for coloring food stuffs, oils and dying wool and in medicinal preparations. This review emphasizes the distribution, morphology, phytochemical constituents, ethnopharmacology, which may help in future research.
Keywords: Alkannin; hispidone; naphthoquinones; Ratanjot; shikonin